1990
DOI: 10.1152/jn.1990.63.4.689
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory responses of single neurons in the insula of the macaque monkey

Abstract: 1. In recordings made from 2,925 single neurons, a region of primary taste cortex was localized to the rostral and dorsal part of the insula of the cynomolgus macaque monkey, Macaca fascicularis. The area is part of the dysgranular field of the insula and is bordered laterally by the frontal opercular taste cortex. 2. The responses of 65 single neurons with gustatory responses were analyzed in awake macaques with the use of the taste stimuli glucose, NaCl, HCl, quinine HCl (QHCl), water, and black currant juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
150
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(166 citation statements)
references
References 27 publications
12
150
1
3
Order By: Relevance
“…That is, a primary taste cortex resides in the rostral insula and adjoining frontal operculum (189)(190)(191)(192). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus is of reward value (193).…”
Section: Feeding Behaviormentioning
confidence: 99%
“…That is, a primary taste cortex resides in the rostral insula and adjoining frontal operculum (189)(190)(191)(192). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus is of reward value (193).…”
Section: Feeding Behaviormentioning
confidence: 99%
“…Rolls and colleagues28 have demonstrated that neurons in the OFC of the macaque represent the reward value of tastes. Taste neurons in the OFC, in contrast to neurons in the primary taste cortex,29,30 stop responding to the taste of a food if the monkey is fed to satiety with that food 31. Also, monkeys will work to receive electrical stimulation of the OFC if they are hungry, but not if they are satiated 32,33.…”
Section: The Functions Of the Brain Areas Involved In Ocdmentioning
confidence: 99%
“…Brain imaging studies performed in the past decade in human and nonhuman primates show that a primary taste cortex resides in the rostral insula and adjoining frontal operculum (Scott et al, 1986;Yaxley et al, 1990;Faurion et al, 1999;Schoenfeld et al, 2004). Some studies argue that these regions provide a representation of food in the mouth that is independent of hunger, and thus of reward value (Rolls, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This concentration is present in soft drinks and is a level of sweetness preferred by the general public (Drewnowski et al, 1987;Sunday and Halmi, 1990). In primates and healthy humans, both sugar (Rolls, 2005) and water (Scott et al, 1986;Yaxley et al, 1990;Zald and Pardo, 2000;De Araujo et al, 2003a) ingestion activates neurons in the primary and secondary cortical taste areas. We hypothesize that AN women might have a disturbance of these higher order pathways modulating the sensory and hedonic aspects of feeding.…”
Section: Introductionmentioning
confidence: 99%